Measuring Indonesia's Sustainability Transition: A Literature Review Of Green, Blue, Environmental, And Regional Competitiveness Indices - Pardomuan Robinson Sihombing (International Journal of Economics, Science, and Education, 2026)
The transition to sustainable development is a crucial agenda for Indonesia in achieving its 2045 Golden Indonesia Vision. The government has developed a series of composite indices to measure progress and identify challenges. This paper presents a systematic literature review of four major sustainability indices in Indonesia: the Green Economy Index (GEI), the Indonesian Blue Economy Index (IBEI), the Environmental Quality Index (EQI), and the Regional Competitiveness Index (RCI). Using a literature review method that synthesizes government reports, official publications, and academic journals, this study analyzes each index's conceptual framework, methodology, and key findings. The results of the analysis reveal a complex and sometimes contradictory narrative. On the one hand, the GEI shows a trend of progress driven by improvements in the socio-economic pillar. On the other hand, the environmental pillar is consistently the weakest, and the EQI shows volatility in marine water quality (MWQ), indicating a gap between blue economy ambitions and the reality of ecosystem health. Furthermore, the IBEI has a relatively low initial national score (43.98). Meanwhile, the RCI highlights sharp regional competitiveness gaps, which have the potential to become structural barriers to the implementation of inclusive sustainable development at the national level.